Digitalising yoruba orthography instruction using interactive e-content (2020)
This study examined the effects of interactive e-content package, intelligent quotient and language orientation on students' achievement in Yoruba orthography. The study adopted the pretest-posttest, control group, quasi experimental design with a 3x3x2 factorial matrix. Participants were 80 JSS II students (in intact classes of two public schools randomly selected from two Local Government Areas in Oyo State. Two instruments, Yoruba Language Achievement Test (r=0.69) and Language Intelligence Quotient Test (r=0.5) were used while three hypotheses were tested at 0.05 level of significance. Data were analysed using ANOVA. Results showed significant effects of treatment, language orientation and intelligence quotienton students' achievement in Yoruba orthography The study concludes that teachers should consider language orientation and intelligence quotient in using e-packages for Yoruba orthography instruction. Therefore, teachers should adopt Yoruba interactive e-content package for the teaching of Yoruba orthography to improve achievement in Yoruba language.